CIÊNCIAS DO ESPORTE - Detoni, Guilherme Cesca; de Oliveira, Vin{\'ıcius Machado; Ferreira, Cristhian; Queiroga, Marcos Roberto; Peyré-Tartaruga, Leonardo Alexandre; Tartaruga, Marcus Peikriszwili (2015)
n/a
n/a